1998
DOI: 10.1161/01.str.29.8.1539
|View full text |Cite
|
Sign up to set email alerts
|

Migrainous Visual Accompaniments Are Not Rare in Late Life

Abstract: Background and Purpose-Questionnaires to elicit symptoms of transient ischemic attacks (TIAs) may detect late-life transient visual symptoms similar to the visual aura of migraine, often without headache. We determined the frequency, characteristics, and stroke outcome of these symptoms in the Framingham Study. Methods- During 1971During -1989, at biennial examinations, 2110 subjects of the Framingham cohort were systematically queried about the occurrence of sudden visual symptoms. Results-Visual migrainous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 24 publications
1
37
1
1
Order By: Relevance
“…The Framingham Study (Wijman et al, 1998) demonstrated that these migrainous visual accompaniments occur in just over 1% of the population aged between 30 and 62 years. This study showed that the mean age of onset of these symptoms was 56 years and in 58% of subjects no headache was reported.…”
Section: Visual Auramentioning
confidence: 99%
“…The Framingham Study (Wijman et al, 1998) demonstrated that these migrainous visual accompaniments occur in just over 1% of the population aged between 30 and 62 years. This study showed that the mean age of onset of these symptoms was 56 years and in 58% of subjects no headache was reported.…”
Section: Visual Auramentioning
confidence: 99%
“…Pilot testing involved 76 participants (34 male; mean age 60 years, range 23-92; 51 with postsecondary education) and resulted in revisions to three items. 3. Repeat testing of the three revised items involved 36 participants (15 male; mean age 56 years, range 32-84; 30 with postsecondary education) and resulted in no further modification.…”
Section: Strokementioning
confidence: 99%
“…Boesen, ME 1,3 Background: Early detection and treatment of atrial fibrillation (AF) could prevent many strokes. New technology devices enable simple, rapid, inexpensive AF screening without requiring standard 12-lead ECG or medical personnel.…”
Section: P1005 Carotid Artery Distensibility Evaluation With Dynamicmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for patients aged ≥60 years among whom transient ischemic attack occurrence increases, whereas attacks of MA are more likely to become more atypical because they are not always followed by a migraine headache. 52 The sudden onset of transient ischemic attack symptoms paired with the presence of vascular risk factors is the strongest difference from MA, which has a more gradual-progressing occurrence of symptoms. The presence of a headache after transient neurological symptoms does not necessarily mean that these symptoms are consistent with a diagnosis of MA, because a migraine-like attack can be triggered by ischemic vascular events.…”
Section: The Clinical Challenge: Migraine Aura Versus Transient Ischementioning
confidence: 99%